Application of the “success to the successful” archetype in a case study to demonstrate the importance of benefits management in the program management - Sales, Luciano da Silva Bastos (2017)
Many organizations still run programs as large projects. Such organizations are unable to properly manage benefits, which is the key feature program management can deliver. The practical consequence of such a gap in program management understanding is that projects that should work together in a coordinated fashion, aiming to deliver the maximum benefits, end up instead competing one against another. In this work, we argue that this situation fits into the Success to the Successful archetype, which is just one of system archetypes in which an organization can fall in due to improper program management. Falling into such a trap thus represents compromising organizations' internal decision structures as well as overshadowing long-term potential benefits that could be derived from the initiatives they are carrying out. We use the Connected Amazon Program, a Brazilian Government initiative as case study. Using real data, we use System Dynamics to model and run a simulation that demonstrates the results obtained before and after a proper program' structure was in place. In practice, it was identified that the incorporation of program management practices can improve decision making in the strategic initiatives, thus avoiding that projects' delivered capabilities will never become benefits for the organizations involve.